Development of closed-loop control system for microwave freeze-drying of carrot slices - Sujinda, Narathip (2021)
Microwave freeze-drying (MFD) is the process that applies the microwave as the energy source to freeze-dry the food product. It is a complex process due to the combination of microwave power, vacuum pressure, drying time, material temperature and moisture content that affects the drying rate, product quality, and energy consumption. The proper control of MFD process conditions to achieve the optimum drying performance and quality of products is a challenge for researcher. Therefore, the objective of this research was to design the MFD process strategy called dynamic microwave logic control (DMLC) and integrated into the closed-loop control (CLC) system for improving the MFD performance. In the first part of this research, the uncertainty of the measurement system and moisture content calculation was evaluated following the Guide to the expression of uncertainty in measurement or GUM (ISO, 2008) to verify the accuracy of the measurement systems and the calculation of the moisture content. The results show that the uncertainty of temperature measurement is ±1.5oC or 3.9% from full scale range of 30 – 50oC, the uncertainty of weight measurement is ±0.347 grams or 0.8% from full scale range of 0 – 150 grams, and the uncertainty of real-time moisture content calculation is ±1% (wet basis). As the results, the measurement systems were acceptable for using in the CLC system with no affected in terms of process control and product quality which confirm by the same later results in repetition of each treatment in this research. In the second part, the temperature variations during MFD of carrot slices was study by applying the closed-loop temperature control (CLT) system to control the carrot slices temperature in the final stage of MFD process. The MFD with CLT can improved the temperature control efficiency up to 60% compared to the MFD without CLT while provided the product quality similar to freeze drying (FD). Therefore, the CLT was applied to use with the MFD process for develop CLC system in the final part of this research. In the final part, the CLC system was developed to improve the MFD process and to examine the effects of a DMLC on the drying characteristics of MFD. The development consists of two sections. In the first section, the MFD process was examined to obtain the strategy for drying the carrot slices using microwave powers of 100 W, 200 W, and 300 W, with a temperature profile of the sample from -15oC to 40oC, and the final moisture content of 6% (wet basis). In the second section, the DMLC was strategically developed based on a drying-phase configuration and dynamic control between the microwave power and real-time moisture content sensing to provide feedback to the CLC system. After developed the DMLC, it was integrated into the CLC system. The results showed that applying the DMLC into the control logics, the CLC can work properly in MFD process by shortened the drying time by 62.4% and 23.4% compared with those of FD and MFD with no DMLC, respectively. The MFD-DMLC provided the final product with a quality equivalent to that of the FD process but achieved the 44.3% better SMER, which indicated the more efficient drying process with lower energy consumption. The findings from this research suggested that the DMLC based on the moisture content and temperature of the samples could be combined with the MFD process to enhance its efficiency while maintaining the superior quality of the FD process.